Bordetella pertussis diagnosis in children under five years of age in the Regional Hospital of Cajamarca, Northern Peru - Del Valle Mendoza, Juana Mercedes (2015)
Introduction: Bordetella pertussis is an important human pathogen that causes whooping cough (pertussis), an endemic illness responsible of significant morbidity and mortality, especially in infants and children. Worldwide, there are an estimated of 16 million cases of pertussis, resulting in about 195,000 child deaths per year. In Peru, pertussis is a major health problem that has been on the increase despite immunization efforts. The objective of this study was to determine the prevalence of B. pertussis among children under five years of age suspected to have whopping cough in Cajamarca, Peru. Methodology: Children diagnosed with whooping cough admitted to the Hospital Regional de Cajamarca from August 2010 to July 2013 were included. Nasopharyngeal samples were obtained for B. pertussis culture and polymerase chain reaction (PCR) detection. Results: In 133 children, the pertussis toxin and IS481 gene were detected in 38.35% (51/133) of the cases by PCR, while only 9.02% (12/133) of the Bordetella cultures were positive. The most frequent symptoms in patients with positive B. pertussis were paroxysm of coughing 68.63% (35/51), cyanosis 56.86% (29/51), respiratory distress 43.14% (22/51), and fever 39.22% (20/51). Pneumonia and acute bronchial obstructive syndrome were present in 17.65% (9/51) and 13.72% (7/51) of the cases, respectively. Conclusions: B. pertussis is responsible for an important proportion of whooping cough in hospitalized children in Cajamarca. Epidemiologic surveillance programs for B. pertussis are essential in Peru, especially in children who could most benefit from the vaccine.